PENGARUH PENGGUNAAN MODEL PEMBELAJARAN MANTEL SANG AHLI TERHADAP MOTIVASI BELAJAR PPKn SISWA KELAS VII DI SMPN 40 PEKANBARU - Elva Mustika; Zahirman Zahirman; Haryono Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research is based on the low motivation of learning  PPKn of the students at SMPN 40 Pekanbaru. The formulation of the problem in this research is "Is there any significant effect of using Expert coat learning model to students’ motivation in learning PPKn at SMPN 40 Pekanbaru ?". This study aims to determine the effect of using Expert coat learning model to students’ motivation in learning PPKn at SMPN 40 Pekanbaru. This research was conducted at SMPN 40 Pekanbaru in August 2018. This research was a quantitative descriptive which is experimental research which the students of grade VII SMPN 40 Pekanbaru became the population in this study. The sample in this research was taken based on "Random Sampling" technique. Where the class taken into the sample was students of class VII C (experimental class) given the learning model of Expert coat, and class VII D (control class) were students who were given the conventional method. Then data analysis by using homogeneity test and "t" test. Based on the result of research indicated that there was an effect of learning motivation between student who using Expert coat learning model and conventional method in SMPN 40 Pekanbaru (  > ). Where there was an average increase to motivation in learning PPKn of experimental class  from 20,23 to 22,23 and the average of PPKn learning motivation of control class from 16,07 to 19,13. Thus the hypothesis which reads that there is an effect of using Expert coat learning model to students’ motivation in learning PPKn at SMPN 40 Pekanbaru, can be accepted. Keywords: Expert Coat, Learning Motivation